The representation of ukranian refugees in media discourse - Belalia, Ouiam Amira Hadil (My University, 2023)
This dissertation focuses on the representation of Ukrainian refugees in media discourse through the lens of critical discourse analysis (CDA). The study aims to examine how Ukrainian refugees are portrayed and constructed in three articles from different newspapers. The research employs Van Leeuwen's socio-semantic model as a framework to analyze the linguistic strategies, ideological constructs, and power relations embedded within the representation of Ukrainian refugees. The study begins with a comprehensive review of the literature on critical discourse analysis and its application to media analysis, highlighting the IV relevance of examining media representations in shaping public perceptions and attitudes toward refugees. The specific focus on Ukrainian refugees is justified by their significant presence within global displacement crises and the need for a nuanced understanding of their experiences and challenges. The Key categories of Van Leeuwen’s model include nomination, categorization, evaluation, exclusion, inclusion, functionalization, personalization, impersonalization, and identification. This socio-semantic inventory is used to uncover the underlying linguistic and visual representations of Ukrainian refugees in the media. The findings reveal the linguistic strategies employed in the representation of Ukrainian refugees and their implications in shaping public understanding and empathy towards this marginalized group. The analysis highlights potential biases, stereotypes, and power dynamics within the media discourse, emphasizing the need for more accurate and responsible portrayals. This dissertation contributes to the field of discourse studies by providing a detailed examination of the representation of Ukrainian refugees in the media. The findings offer insights into the power relations and ideological constructs that shape media narratives, aiming to promote a more inclusive and informed public discourse surrounding refugee issues.
a critical discourse analysis of three newspapres articles
Keywords: Ukrainian refugees; media representation; critical discourse analysis; Van Leeuwen's socio-semantic model; power relations; ideological constructs